INTERRELATIONSHIP OF CLINICOPATHOLOGICAL FEATURES OF BREAST CANCER AMONG DIFFERENT ETHNIC GROUPS (Jurnal Teknologi (Sciences & Engineering), 2016)
Breast cancer is a heterogeneous disease that can be classified using a variety of clinical and pathological features. In Malaysia, breast cancer remains the most prevalence malignancy among women which vary substantially by racial/ ethnic group. A pilot study was conducted to determine clinical characteristics of breast cancer (BrCa) and the association with demographic factors from a set of data retrieved from Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia (n = 236). In this study, 55.1% of the patients were Malay followed by Chinese (33.9%) and Indian (11.0%). By using Pearson Chi-Square test, it was reported that ethnicity was significantly associated with age at diagnosis (p = 0.001) and family history (p = 0.034). In addition, interrelationships (p value < 0.05) existed between: (1) ethnics with age at diagnosis (2) ER with PR, TNM staging and grading (3) PR with tumor grading. In summary, interrelationships status of BrCa clinicopathological features can be used to better understand BrCa in predicting prognosis for the patients.